Praktik Foto Prewedding di Kabupaten Aceh Utara : Analisis Fiqh Syāfi‘Iyyah Dan Qanun Aceh Nomor 6 Tahun 2014 Pasal 1 Ayat 24 Tentang Ikhtilat - Afrizal M. Ali; Husni Husni; Safriadi Safriadi (Ma'had Aly Raudhatul Ma'arif, 2026)
The development of the wedding industry in the digital era has given rise to a new tradition in the form of prewedding photography before the marriage contract. In North Aceh Regency, this phenomenon is no longer merely a documentation need but has transformed into a visual popular culture frequently published on social media, thereby triggering the issue of